2020
DOI: 10.1111/nmo.13838
|View full text |Cite
|
Sign up to set email alerts
|

High‐fat diet–induced alterations to gut microbiota and gut‐derived lipoteichoic acid contributes to the development of enteric neuropathy

Abstract: BackgroundHigh‐fat diet, microbial alterations and lipopolysaccharide (LPS) are thought to cause enteric diabetic neuropathy and intestinal dysmotility. However, the role of the gut microbiota, lipoteichoic acid (LTA) from Gram‐positive bacteria and short‐chain fatty acids (SCFAs) in the development of diabetic enteric neuropathy and intestinal dysmotility is not well understood. Our aim was to examine the role of the gut microbiota, LTA and SCFAs in the development of diabetic enteric neuropathy and intestina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 61 publications
1
25
0
1
Order By: Relevance
“…In addition to obesity, other inflammatory conditions such as periodontal disease, obstructive pulmonary disease, arthritis, and muscular dystrophy are also associated with the development of IR and type 2 diabetes mellitus (T2DM; Demmer et al, 2008; McNeely & Boyko, 2004; Tiengo et al, 2008). Notably, most studies involving this T2DM and IR were performed using obese humans or animals fed a high‐calorie diet that resembles the western human diet (Lowette et al, 2016; Masi et al, 2017; Nyavor et al, 2020). However, not all patients with T2DM are obese.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to obesity, other inflammatory conditions such as periodontal disease, obstructive pulmonary disease, arthritis, and muscular dystrophy are also associated with the development of IR and type 2 diabetes mellitus (T2DM; Demmer et al, 2008; McNeely & Boyko, 2004; Tiengo et al, 2008). Notably, most studies involving this T2DM and IR were performed using obese humans or animals fed a high‐calorie diet that resembles the western human diet (Lowette et al, 2016; Masi et al, 2017; Nyavor et al, 2020). However, not all patients with T2DM are obese.…”
Section: Introductionmentioning
confidence: 99%
“…These abnormalities occur in prediabetes and diabetic patients, and disrupted mucosal barrier promotes an abnormal passage of luminal substances into the intestinal wall 43,44 . We recently reported that HFD‐induced changes to gut microbiota composition play a role in HFD‐induced neuropathy and dysmotility 45 . Additionally, changes to gut microbiota composition have been linked to the production of toxic molecules causing decreased colonic muscle contractility in irritable bowel disease, 46 and visceral hypersensitivity in colicky infants 47 .…”
Section: Discussionmentioning
confidence: 99%
“…43,44 We recently reported that HFD-induced changes to gut microbiota composition play a role in HFD-induced neuropathy and dysmotility. 45 Additionally, changes to gut microbiota composition have been linked to the production of toxic molecules causing decreased colonic muscle contractility in irritable bowel disease, 46 and visceral hypersensitivity in colicky infants. 47 Furthermore, there is an increasing number of studies providing evidence to link CNS neurologic diseases, notably autism spectrum disorder, Parkinson's disease, and Alzheimer's disease to altered gut microbiota and GI dysfunctions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Changes in the number of intestinal cells of Cajal and myenteric neurons due to impaired mucosal integrity and low baseline impedance in the duodenum which result in abnormal gastroduodenal motility, have been reported in patients with FD [ 15 , 16 ]. Alternatively, a high-fat diet and microbial alteration are thought to cause enteric diabetic neuropathy and intestinal dysmotility based on the reduction of nitrergic myenteric neurons per ganglion in the duodenum [ 17 ]. The median time of retention in the duodenum was reported to be longer in diabetic patients than in healthy volunteers (12.7 versus 8.1 minutes) [ 18 ].…”
Section: Discussionmentioning
confidence: 99%